2015
DOI: 10.12678/1089-313x.19.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Compensated Turnout Characteristics and their Relationship to Injuries in University Level Modern Dancers

Abstract: Dancers may compensate alignment at the spine, hip, knees, ankles, and feet to achieve a greater turnout than is available at the hip alone. Such compensations are believed to lead to many of the musculoskeletal injuries experienced by dancers, especially overuse injuries. The aim of this study was to explore the relationship between compensated turnout and injury of the lower extremities and low back. Twenty-two university level modern dancers age 19 to 23 participated. Measurements were taken of active hip e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 16 publications
2
42
1
Order By: Relevance
“…The measurement of the dancers' turnout with the subject standing on a piece of paper or soil or whiteboard, used by 9 out of the 25 studies found by this systematic review 1,20,21,39,43,[46][47][48]50 , is characterized as a static evaluation and, considering the friction of the subjects' feet with the soil, can interfere with the found values for turnout. Therefore, to dynamically evaluate the turnout and to eliminate the influence of this friction on its values, six studies used no-friction rotational discs to measure it 20,38,42,[49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the dancers' turnout with the subject standing on a piece of paper or soil or whiteboard, used by 9 out of the 25 studies found by this systematic review 1,20,21,39,43,[46][47][48]50 , is characterized as a static evaluation and, considering the friction of the subjects' feet with the soil, can interfere with the found values for turnout. Therefore, to dynamically evaluate the turnout and to eliminate the influence of this friction on its values, six studies used no-friction rotational discs to measure it 20,38,42,[49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the turnout capacities in dancers has been the focus of many research studies which have predominantly focused on the relationship between turnout in a standing position and the active and passive hip joint external rotation ranges of motion 10,27–30. The results of the present study reported turnout angles during rise and sissonne to be greater than those reported in previous research studies 10,27,28,30. However, the turnout angle of sissonne is likely overestimated due to the oblique anteriorly tilted position of the pelvis during the task that results during from the hip extension of the opposite leg.…”
Section: Discussionmentioning
confidence: 99%
“…1,[83][84][85] Many of the injuries of dancers usually occur during jumps, lifts, and high impact movements. 86 Shah 83 contributed to understanding dance injuries by analyzing injuries within professional modern dancers. She found that 18% of the total injuries of have been related to the ankle.…”
Section: Dance Biomechanicsmentioning
confidence: 99%
“…95 Most dancers would like a turnout of about 180 degrees. 86 Sometimes dancers want to compensate alignment in the spine, hip, knee, and feet in order to achieve that perfect turnout. 86 These compensations have been shown to have a high contribution to overuse injury in dance.…”
Section: Dance Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation